Psychological attitudes of Indonesian millenials consumer to choose Islamic banking financing - Moh. Herman Eko Santoso; Mohamad Soleh Nurzaman (Universitas Negeri Surabaya, 2023)
Islamic banks define as financial service institutions which offer the ease of owning home through Islamic homeownership financing products as knows as Islamic mortgage. This financing product can be a solution for millennials to be able to own a home. This study aims to examine the psychological response of millennials generation towards acceptance in choosing an Islamic mortgage using Theory of Planned Behavior Model (TPB) with Attitude, Subjective Norm, and Perceived Behavioral Control as variables. Analyzed of 256 respondents in this study used Structural Equation Modelling AMOS (SEM-AMOS) and IBM SPSS Statistics. The research shows that the variable Attitude and Perceived Behavioural Control have positive and significant impact on the intention of millennials to choose Islamic mortgage. Further, Perceived Behavioral Control was found to be the most influential factor in determining the intention of millennials to choose Islamic mortgage. On the other hand, this study also found that the Subjective Norm variable had a positive but not significant for the effect. These findings provide information that psychological factors can form the customer's intention to use Islamic mortgage products. Therefore, all stakeholders can consider the psychological factors of prospective customers in designing and developing Islamic mortgage products in Indonesia.